THEORETICAL PERSPECTIVES ON POVERTY: A CRITICAL REVIEW - Dr. JOYEETA AHMAD (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
It is significant to understand that theoretical elements permeate process of the conceptualization, measurement and explanation of a social problem including the application of a remedial policy to confront the issue. Thus all anti-poverty programmes are formulated within a distinct frame of reference which guide the policy framers to systematize and thus actualize their approach.